Low dose lung radiotherapy for COVID-19 pneumonia. The rationale for a cost-effective anti-inflammatory treatment. (July 2020) - Lara, Pedro C.; Burgos, Javier; Macias, David
Highlights: SARS-CoV-2 pneumonia severely ill patients, develop a systemic inflammatory response characterized by a sudden increase in several pro-inflammatory cytokines, mainly IL-1, IL-6 and TNF-alfa by activated M1 macrophages. COVID-19 patients, develop a systemic cytokine inflammatory response Drug blockade of IL-6/IL-1 and respirator equipment is not offered to all patients. Low dose radiotherapy (0, 5 Gy), is an evidence-based anti-inflammatory treatment LDRT that could modify the immune landscape in the affected lung. LDRT is a cost-effective non-toxic treatment available in most general hospitals. Abstract: The COVID-19 pandemia is affecting people worldwide. Most of the patients suffered of a respiratory disease that will progress to an acute respiratory distress syndrome (ARDS). SARS-CoV-2 pneumonia severely ill patients, develop a systemic inflammatory response with a Cytokine Release Syndrome (CRS), that is characterized by a sudden increase in several pro-inflammatory cytokines, mainly IL-1, IL-6 and TNF-alfa by activated macrophages (M1 phenotype). Blocking IL-6 with tocilizumab and using respirator equipment seems to be a very important issue in this (SARS-CoV-2) pneumonia, but not all patients are referred to such treatments. Low dose radiotherapy (0, 5 Gy), is an evidence-based anti-inflammatory treatment, that could modify the immune landscape in the lung affected of SARS-CoV-2 pneumonia, through macrophages polarization to alternatively activated Macrophages (M2 phenotype). Radiation-induced cancer risk could be assumed due to the very low dose used, the advanced age of the patients and the life-threatening condition of SARS-Cov2 pneumonia. LDRT is a cost-effective non-toxic treatment already available in most general hospitals. This fact allows that it would be used for the large number of patients that will suffer this disease, and that would not receive specific anti-IL-6 treatments in ICUs in low and middle income countries.